THE EFFECT OF EDUCATIONAL BACKGROUND ON THE QUALITY OF LIFE OF THE PRE-ELDERLY POPULATION - Andriani, Dian Sri; Putri, Rani Mega; Saputra, Ardi (Universitas Airlangga, 2024)
The quality of life of the pre-elderly population is the key to readiness to enter the stages of old age to realize a prosperous life. Previous research has extensively studied the condition of the elderly population in various scientific disciplines but still minimally examines the quality of life of the pre-elderly population, especially regarding educational background as an indicator of human resource development. This research aims to measure and analyze the influence of educational background on the quality of life of the pre-elderly population as they enter old age. This research method is quantitative with the instrument used being a questionnaire. This research population was residents in Timbangan Sub District, Ogan Ilir Regency aged 45-59 years. The sample calculation used the Isaac and Michael formula with a sampling error of 5% so that the sample size for this study is 310 residents. Data analysis used in this research is the independent sample median K test, Tukey test, and ordinal regression test using SPSS version 20 and STATA version 17 software. The results show that there is a significant influence between educational background and the quality of life of the pre-elderly population in Timbangan Sub District, Ogan Ilir Regency, it was 7.16%. Thus, educational background variables can contribute to improving the quality of life of the pre-elderly population in Timbangan Sub District, Ogan Ilir Regency.